National, clinical cohort study of late effects among survivors of acute lymphoblastic leukaemia: the ALL-STAR study protocol. Issue 2 (9th February 2021) - Andrés-Jensen, Liv; Skipper, Mette Tiedemann; Mielke Christensen, Kristian; Hedegaard Johnsen, Pia; Aagaard Myhr, Katrine; Kaj Fridh, Martin; Grell, Kathrine; Pedersen, A. M. L.; Leisgaard Mørck Rubak, Sune; Ballegaard, Martin; Hørlyck, Arne; Beck Jensen, Rikke; et al.
Abstract : Introduction: More than 90% of patients diagnosed with childhood acute lymphoblastic leukaemia (ALL) today will survive. However, half of the survivors are expected to experience therapy-related chronic or late occurring adverse effects, reducing quality of life. Insight into underlying risk trajectories is warranted. The aim of this study is to establish a Nordic, national childhood ALL survivor cohort, to be investigated for the total somatic and psychosocial treatment-related burden as well as associated risk factors, allowing subsequent linkage to nation-wide public health registers. Methods and analysis: This population-based observational cohort study includes clinical follow-up of a retrospective childhood ALL survivor cohort (n=475), treated according to a common Nordic ALL protocol during 2008–2018 in Denmark. The study includes matched controls. Primary endpoints are the cumulative incidence and cumulative burden of 197 health conditions, assessed through self-report and proxy-report questionnaires, medical chart validation, and clinical examinations. Secondary endpoints include organ-specific outcome, including cardiovascular and pulmonary function, physical performance, neuropathy, metabolic disturbances, hepatic and pancreatic function, bone health, oral and dental health, kidney function, puberty and fertility, fatigue, and psychosocial outcome. Therapy exposure, acute toxicities, and host genome variants are explored as risk factors. Ethics and dissemination: The study is approved by the Regional Ethics Committee for the Capital Region in Denmark (H-18035090/H-20006359) and by the Danish Data Protection Agency (VD-2018–519). Results will be published in peer-reviewed journals and are expected to guide interventions that will ameliorate the burden of therapy without compromising the chance of cure.